The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/939504
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Sorption Characteristics of Corn Stover and Big Bluestem

Abstract: Moisture content is an important feedstock quality in converting it into energy through biochemical or thermochemical platforms. Knowledge of moisture sorption relationship is useful in drying and storage to preserve the quality of feedstocks. Moisture sorption isotherms for potential feedstocks such as corn stover and big bluestem are missing. EMC values of corn stover and big bluestem were determined using static gravimetric technique with saturated salt solutions (ERH 0.12–0.89) at different temperatures (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…At harvest, the moisture content of woody biomass is around 50%, while that of agricutltural residues is typically about 20% . The amount of water in biomass affects size reduction, drying, transport, storage, processing, and physiochemical conversion for biofuels or bio-oil . Most postharvest operations require moisture contents to be below 20% for optimum performance. ,, However, some studies have suggested a relationship between increased water mobility in biomass microstructure and reduced recalcitrance in downstream conversion processes, leaving biorefineries with a difficult choice one way or the other …”
Section: Geometric and Volumetric Propertiesmentioning
confidence: 99%
“…At harvest, the moisture content of woody biomass is around 50%, while that of agricutltural residues is typically about 20% . The amount of water in biomass affects size reduction, drying, transport, storage, processing, and physiochemical conversion for biofuels or bio-oil . Most postharvest operations require moisture contents to be below 20% for optimum performance. ,, However, some studies have suggested a relationship between increased water mobility in biomass microstructure and reduced recalcitrance in downstream conversion processes, leaving biorefineries with a difficult choice one way or the other …”
Section: Geometric and Volumetric Propertiesmentioning
confidence: 99%
“…Moisture content represents the quantity of water in biomass, expressed as a percentage of the material weight. It has a strong influence not only on harvest and preparation, but also on transport, storage, processing, and the resultant products [85]. The moisture in biomass can remain in external and inherent forms.…”
Section: General Introductionmentioning
confidence: 99%
“…The commonest limitation on the shelf life of food is microbial growth; hence, several preservation processes are aimed at achieving microbial stability of foods [ 19 , 20 ]. Water activity of a foodstuff is defined as the ratio of vapour pressure of water in the food to vapour pressure of pure water at the same temperature [ 17 , 21 ]. The moisture content of most foods increases curvilinearly (frequently sigmoidal) with water activity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%